Dampak Cyberbullying terhadap Kesehatan Mental Mahasiswa Baru di Universitas Halu Oleo - Hannin Pradita Nur Soulthoni; Dian Puspita Rizki (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The psychological impact of cyberbullying on new students in the Social Welfare Study Program at Universitas Halu Oleo is the main focus of this study. The purpose of this research is to understand how the experience of cyberbullying affects the mental well-being of students who are adapting to campus life. A qualitative approach with a phenomenological design was used, where data were collected through in-depth interviews with students who had been victims of cyberbullying. The findings of the study indicate that cyberbullying significantly impacts three key psychological aspects: anxiety, depression, and self-esteem. The majority of the students interviewed reported ongoing anxiety, worrying about further dissemination of personal information. Depression was also found to be a common impact, with students feeling a loss of motivation and isolation from their peers. Additionally, nearly all participants reported a significant decline in self-esteem after experiencing online bullying. Based on these findings, the study recommends developing cyberbullying prevention programs on campus and providing more accessible psychological support services. It is hoped that these efforts will help new students overcome the psychological effects of cyberbullying and enable them to navigate their transition to university life in a healthier social and academic environment.